2005
DOI: 10.1093/jxb/eri246
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate stimulates the de novo biosynthesis of vitamin C in plant cell suspensions

Abstract: Vitamin C (L-ascorbic acid) is an important primary metabolite of plants that functions as an antioxidant, an enzyme cofactor, and a cell-signalling modulator in a wide array of crucial physiological processes, including biosynthesis of the cell wall, secondary metabolites and phytohormones, stress resistance, photoprotection, cell division, and growth. Plants synthesize ascorbic acid via de novo and salvage pathways, but the regulation of its biosynthesis and the mechanisms behind ascorbate homeostasis are la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(164 citation statements)
references
References 81 publications
10
139
0
2
Order By: Relevance
“…The response of carbohydrate-related gene expression to girdling might be subjected to the regulation of sugar as a signal (Li et al 2003a, b). Some reports in other crops pointed out that the expression of AA-related genes was stimulated by feeding sucrose or methyl jasmonate (Nishikawa et al 2005;Wolucka et al 2005). In this study, we found that the sucrose content was significantly increased at 20 DAT (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…The response of carbohydrate-related gene expression to girdling might be subjected to the regulation of sugar as a signal (Li et al 2003a, b). Some reports in other crops pointed out that the expression of AA-related genes was stimulated by feeding sucrose or methyl jasmonate (Nishikawa et al 2005;Wolucka et al 2005). In this study, we found that the sucrose content was significantly increased at 20 DAT (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Such a mechanism may allow plants to promote growth in the evening with less-active JA signaling and restrict growth in the morning when JA response is more active. Oxidative stress caused by the dark-tolight transition is one example of a daily event in which JA signaling is vital to plants (Sasaki-Sekimoto et al, 2005;Wolucka et al, 2005;Dombrecht et al, 2007). In previous genomic analysis, clock-regulated genes responsive to the reactive oxygen species or to oxidative damage were shown to be expressed early in the morning phase (Covington et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Damaging of membranes fatty acids could produce small hydrocarbon fragments including MDA which is an important sign of membrane system injury (Masood et al, 2006 andMoussa, 2008). Ascorbic acid is an important water-soluble antioxidant and cell moderator in physiological processes including photoprotection (Wolucka, 2005 andKhan &Ashraf, 2008) where, it can rapidly react with radical intermediates of an autoxidation chain and stop it (Khan, 2006). Latef (2014) reported that salt stress induced oxidative stress by increasing malondialdehyde (MDA) content and activity of peroxidase.…”
Section: Antioxidant Defense Systemmentioning
confidence: 99%